Exclusive breastfeeding modifies the association between maternal education and child development: a cross-sectional study nested in a cohort - Luiza Alves Ford; Gabriela Buccini; Amanda Castelo Saragosa; Isadora de Araújo Martins; Janaína Matos Moreira; Stela Maris Aguiar Lemos; Claudia Regina Lindgren Alves; Vivian Mara Gonçalves de Oliveira Azevedo (Jornal de Pediatria)
Objective: Low maternal education is a risk factor for early childhood development (ECD), while exclusive breastfeeding (EBF) is a protective factor. This study examined the association between maternal education and ECD outcomes such as cognitive, language, and motor domains and whether EBF modifies this association in Brazil. Methods: This cross-sectional study analyzed data from a non-probabilistic sample of 12-month-old infants born during the COVID-19. Moderation analyses using the Mann-Whitney test examined the effect of EBF at 6 months (effect modifier) on the relationship between Bayley-III cognitive, language, and motor scores as well as Bayley Global Score (BGS) (outcomes) and maternal education (independent variable). The effect size (r) from the sensitivity analysis of the effect modifier was estimated. Results: A total of 269 full-term infants were evaluated. Higher maternal education was associated with better cognitive, language, and BGS (p < 0.00). EBF was associated with higher cognitive (p < 0.01), language (p < 0.02), and BGS (p < 0.00). EBF modified the effect of low maternal education (<10 years; and 10–12 years) on cognitive score and BGS. Among mothers with >10 years of education, a large effect size of EBF was observed on the BGS (r = 0.51), and a medium effect size was noted in the cognitive domain (r = 0.38). Conclusion: Higher maternal education is associated with better scores on Bayley-III domains, and EBF can modify the effect of lower maternal education on ECD in Brazil. This is the first study to identify EBF as a mechanism to protect ECD in adverse conditions such as low maternal education.